The Role of Volition in Distance Education: An Exploration of its Capacities - Deimann, Markus; Bastiaens, Theo (International Review of Research in Open and Distributed Learning, 2010)
During the past two decades, volition, defined as the ability to stay task-focused and ward off distractions, has become of special relevance for educational research and practice. It describes how decreased motivation or negative emotions can be dealt with by applying action control strategies. However, despite its potential, an important area of education has neglected volitional considerations: distance education (DE). This seems paradoxical because by its very nature distance education requires a great deal of persistence and effort that is volitional. Consequently, the present paper introduces a conceptual framework built on volitional theories; it aims to augment traditional perspectives and to analyse major challenges to DE, such as dropout rates. The paper reports results from a longitudinal study (September 2007-July 2009) that was conducted to determine the factorial structure of the Volitional Persona Test (VPT), an online instrument to assess volitional competence, and to obtain detailed information on students’ volitional competence at a large DE university and at numerous traditional universities in German-speaking countries. It was demonstrated that the construct of volition can be subdivided into distinct factors, volitional self-efficacy, consequence control, emotion control, and meta-cognition, which may enable the development of support systems that are tailored to learners’ individual needs. Implications for future research are discussed.